Lean Green Building in Subsidized Housing: Capturing Value through Sales Absorption Rather than Price Premium - Mochamad Friza Pahlevi; Sudrajati Ratnaningtya (Politeknik Siber Cerdika Internasional, 2026)
Background: Indonesian subsidized housing operates under a regulated price ceiling that prevents developers from charging a green premium for environmentally improved homes, leaving the economic rationale for green design unclear in this segment, a gap that prior sustainable-business-model research on value capture has rarely addressed. Objective: This study examines how a medium-scale developer captures value from lean green-building features when a price premium is not possible, and proposes capital velocity as an alternative value-capture mechanism for price-regulated housing markets. Methods: A qualitative single-case study of a subsidized housing project in Garut, West Java, draws on internal and practitioner interviews (four internal respondents; 20 buyers), sales-absorption data, and field observation, and applies a two-by-two comparative logic (competence × green design) with member-checked thematic coding; reporting follows the SRQR guideline. Results: Value appears associated primarily with faster sales absorption, about six units per month against zero to three for comparators of similar price, rather than per-unit margin, and buyers are motivated mainly by thermal comfort, perceived quality, and aesthetics rather than environmental awareness, though other factors such as location and developer reputation may also contribute. Conclusion: Lean green design can be made viable in price-capped housing by functioning as an instrument of capital velocity; as a single-firm study with researcher positionality, the findings are analytical and exploratory rather than statistical.